Parameter Fokus Optis Pada Sistem Akuisisi Citra (Optical Focusing Parameters In An Image Acquisition System) - Perpustakaan UGM, i-lib ([Yogyakarta] : Unit Informasi Inovasi Proses Pembelajaran(UI2P2) UGM, 2005)
ABSTRAK One of the problems of obtaining an image of high quality is the availability of an acquisition system with autofocus control in it's optical system. There are some optical focusing parameters which can be used to control the positions of optical lenses to get an image with the best quality. These parameters however present some weakness in searching the optimal point during the lenses position control. The weakness are in computation speed and the presence of a local maximum at it's parameter curve. This research is intended to develop an optical focusing parameter that can be used to increase the speed and to avoid the local maximum This parameter is based on two dimensional Fourier transform approach. The image data are captured with an adjustable focus camera with a resolution of 320x240 and the parameters are computed using Pentium 4 computer. The results show that the parameter computation speed is increased by a factor of about seven and the local maximum is canceled.